Microwave treatment of biological samples for methylmercury determination by high performance liquid chromatography-cold vapour atomic fluorescence spectrometry - Ramalhosa, Elsa (2001)
A simple and rapid microwave-assisted alkaline digestion procedure was developed in combination with high performance liquid chromatography-ultraviolet post-column oxidation-cold vapour atomic fluorescence spectrometric detection for methylmercury determination in biological tissues. Since the stability of methylmercury in methanolic potassium hydroxide solution under microwave irradiation was verified, the microwave-assisted extraction procedure was optimized in terms of quantitative recovery of methylmercury and minimum time required. The alkaline extracts were subjected to clean-up steps with dichloromethane and hydrochloric acid in order to reduce matrix interferences in methylmercury determination. The effects of matrix interferences were checked by comparison of the slopes corresponding to calibration and standard addition curves. The accuracy of the method was evaluated by the analysis of two biological certified reference materials, NRC TORT-2 and BCR 463. The results obtained by the proposed method were in good agreement with the certified values of methylmercury concentration in both materials. The detection limit was 10 mug kg(-1) and the relative standard deviation was < 8% for methylmercury concentrations ranging from 0.15 to 3.0 mg kg(-1).